GE_GERICHTE C/15891/2016 vom 23. Juni 2017 - GE Cour de justice (2017)
PROTECTION DE L'UNION CONJUGALE ; RELATIONS PERSONNELLES ; VISITE ; OBLIGATION D'ENTRETIEN ; ENFANT | CPC.317; CC.173; CC.176; CC.273; CC.276; CC.285;